Report of the FAO regional workshop on port state measures to combat illegal, unreported and unregulated fishing : (Food and Agriculture Organiation of the United Nations, 2008)
The objective fo the workshop was to develop nation capacity and promote bilateral, sub-regional and/or regional coordination so that country will be better placed to strengthen and harmonize port State measure and, as a result, implement the relevant International Plan of Action to Prevent, Deter and Eliminate illegal, Unreported and Unregulated Fishing (IPOA-IUU) tools and the FAO model scheme and contribute to development of a legally-binding instrument on port State measures.